New taxonomic status of the Pseudotachycines procerus guizhouensis Zhu & Shi, 2022 (Rhaphidophoridae: Aemodogryllinae: Aemodogryllini) - Huang, Shihui; Lin, Chun; Luo, Changqing (Zootaxa, 2023)
The genus Pseudotachycines belongs to the tribe Aemodogryllini of the subfamily Aemodogryllinae. In the present paper, we examined the morphological features of male and female adults of the subspecies P. procerus guizhouensis, and suggested that this subspecies should be treated as a separate species. We redescribed the male of P. guizhouensis in detail. The morphological information and some related photographs of the female of this species were provided for the first time in this study. The morphological differentiation between P. guizhouensis and P. procerus was discussed.